Ballistic impact fracture behaviour of continuous fibre reinforced al-matrix composites - Ali, Al-Hamdan; Nimir, Yassin Lutfi Mahmud; Mustafa, Ramadan J. (Hashemite University, 2010)
The materials response under high energy impact loads was studied using a gas gun. The projectiles were pins 1.2-1.5 mm in diameter and weighing 0.347-0.435 g. The projectile velocity was in the range 100–1300 m/s. The remnant load carrying capability of composite samples after high velocity impact tests was measured to quantify high energy impact induced microstructural damage. The composites retained some of their load bearing capacity even after penetration of the projectile, since structural damage caused by projectiles remained localised, preventing catastrophic failure, particularly for continuous fibre reinforced Alpure matrix composites. Penetration by the projectile occurred at impact energy of about 62-65 J for the conditions investigated. The experimental findings show that the energy absorbing capacity of such composites and their ability to withstand a given blow are largely functions of fibre type and greatly influenced by the matrix ductility, fibrematrix interfacial bonding and volume fraction of reinforcing fibre. Understanding crack propagation and damage development under high energy impact loads may open new opportunities for the use of these composites in lightweight armour applications.